Hexaphenyltriphenylene‐Based Multicomponent Metallacages: Host–Guest Complexation for White‐Light Emission. Issue 21 (9th March 2023) - Liu, Haifei; Guo, Chenxing; Zhang, Zeyuan; Mu, Chaoqun; Feng, Qian; Zhang, Mingming
Abstract: A hexaphenyltriphenylene‐based hexatopic pyridyl ligand is designed and used to prepare three hexagonal prismatic metallacages via metal‐coordination‐driven self‐assembly. Owing to the planar conjugated structures of the hexaphenyltriphenylene skeleton, such metallacages show good host–guest complexation with a series of emissive dyes, which have been further used to tune their emission in solution. Interestingly, based on their complementary emission colors, white light emission is achieved in a mixture of the host metallacages and the guests. Abstract : A series of hexaphenyltriphenylene (HPT)‐based metallacages showing intense blue emission both in the solution and solid state were prepared via multicomponent self‐assembly. They can serve as hosts to complex with three planar fluorescent dyes, and bright white light can be generated when they complex with PDI derivatives.